-12x+8y=36

Simple and best practice solution for -12x+8y=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12x+8y=36 equation:


Simplifying
-12x + 8y = 36

Solving
-12x + 8y = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8y' to each side of the equation.
-12x + 8y + -8y = 36 + -8y

Combine like terms: 8y + -8y = 0
-12x + 0 = 36 + -8y
-12x = 36 + -8y

Divide each side by '-12'.
x = -3 + 0.6666666667y

Simplifying
x = -3 + 0.6666666667y

See similar equations:

| 35.84=27.02+294.9*x-373.7x | | -1(2n+3)=2(-4-7) | | 20-2(2w+1)=5w-2(5+w) | | 0*3+4=0*2+3 | | n+9=3n+5*4 | | f/7-8=72 | | 8(t+2)-3(t-4)=6(t-7) | | 6-9x=26-23x | | 2x-175=755 | | 26.6x+76.6x+200x=5513 | | 2x+11=-37-10 | | 60=12x | | 5x+4=4555 | | 8x-8y=-16 | | 2x+5x/9=-30 | | f+13=27 | | 7=q-83 | | 6n-4(n-3)=n+3 | | 3x+7=(5x-4)*2 | | 9+(2/3)x=81 | | -7c(3/4)=65 | | 6-4y=y | | 2a-3=3-4a | | 3a-6=10-a | | (2x-2)2=(3x-2)(x-3) | | 24+2x-x^2= | | 132-6x=2x-20 | | 12x-5=8x-x | | x(p-cv)=cf | | 4t-3=-13-2t | | 5.3+9.2x=7-4x-8.8 | | 1.8x+4.1x=5.7 |

Equations solver categories